Reasons and benefits associated with ISO 9001 - Certification for sugar and ethanol companies - Ferreira, Caio Stockler (2015)
With increasing business competitiveness, companies have sought to adapt their processes and / or products to worldwide established quality standards in order to achieve a greater share of consumers having as favorable aspect the quality assurance of the products and/or services provided. It was observed that companies of different sizes have different challenges regarding the certification however, the degree of difficulty is the same for all of them. The objective of this paper is to verify the reasons for the implementation of ISO 9001, the obstacles encountered during the implementation, the benefits arising from the use of the quality management system and the degree of difficulty to implement this standard. This work was developed based on a survey involving companies certified with ISO 9001:2008 from the productive sector of sugar, ethanol and derivatives of sugarcane, located in all Brazilian states. It was observed that companies of different sizes have different challenges regarding the certification however the degree of difficulty is the same for all of them. Thus, we believe that expected results represent a very important contribution to examining the reasons, benefits and difficulties of the ISO 9001 to both, the companies and certification bodies, and to researchers.